2021
DOI: 10.3390/plants10112306
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Phytochemistry, Genoprotective Activity, and Antitumor Effects of Extracts of the Selected Lamiaceae Species

Abstract: This study was designed to evaluate the genoprotective, antigenotoxic, as well as antitumor potential of methanolic, ethanolic, and aqueous extracts of Melissa officinalis, Mentha × piperita, Ocimum basilicum, Rosmarinus officinalis, Salvia officinalis, and Satureja montana (Lamiaceae), in different model systems. The polyphenols in these extracts were quantified both spectrophotometrically and using HPLC-DAD technique, while DPPH assay was used to assess the antioxidant activity. The genoprotective potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 68 publications
(95 reference statements)
2
11
0
Order By: Relevance
“…Taken together, the results from TPC, DPPH and ORAC assays suggest that leaf ethanol extracts have more potent antioxidant bioactivity potential than stem extracts. This difference in biological properties between the subparts of the plant and as a function of the extraction procedure have already been observed by other research groups in both basil (between leaves and flowers) [ 49 ] and other vegetables [ 50 ]. The phytochemical detected in both parts of the plant are known for their antioxidant potential.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Taken together, the results from TPC, DPPH and ORAC assays suggest that leaf ethanol extracts have more potent antioxidant bioactivity potential than stem extracts. This difference in biological properties between the subparts of the plant and as a function of the extraction procedure have already been observed by other research groups in both basil (between leaves and flowers) [ 49 ] and other vegetables [ 50 ]. The phytochemical detected in both parts of the plant are known for their antioxidant potential.…”
Section: Discussionsupporting
confidence: 61%
“…This anti-oncogenesis property and associated genoprotective effects would be mainly correlated with basil impact on oxidative stress and NO modulation rather than TNF. Therefore it might be suggested that the absence of variation of the latter cytokine in our assay, for both leaves and stems, might be considered as in accordance rather than as a discrepancy regarding the biological potential of Ocimum basilicum [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…At high concentrations, polyphenolic compounds exhibit pro-oxidant and cytotoxic properties. At the same concentrations in tumor and normal cells, polyphenols can induce oppositely directed effects ( Oalđe Pavlović et al, 2021 ).…”
Section: Chemosensitization Of Tumors With Polyphenolsmentioning
confidence: 99%
“…Resveratrol Human herpesvirus 1 and Human herpesvirus 2 ND Significantly reduced skin lesions, and the effectiveness of the drug depended on its concentration, the time of initiation of treatment and the number of applications per day (Docherty et al, 2004), (Docherty et al, 2005) Epigallocatechin Pavlović et al, 2021). EGCG inhibits ROS generation in normal epithelial cells but induces ROS generation in tumor cells.…”
Section: Mechanism Of Action Referencesmentioning
confidence: 99%
“…Ultrasound-assisted extraction, microwave-assisted extraction, and supercritical fluid extraction belong to a group of novel extraction methods (Jovanović et al, 2017a). The ultrasoundassisted extraction (UAE) has previously been employed by Oal de Pavlović et al (2021), in order to obtain S. montana extracts for further determination of their biological activities, such as antioxidant capacity, antitumor potential and genoprotective activity in acellular system. Ultrasound waves are high-frequency sound waves that are above the human hearing threshold or 20 kHz.…”
Section: Introductionmentioning
confidence: 99%